CIPP Model Evaluation of a Collaborative Diabetic Management in Community Setting - Thanakamon Leesri; Wichit Srisuphan; Wilawan Senaratana; Taweeluk Vannarit; Kittipan Rerkasem (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
Diabetic management requires a continuous assessment of performance, looking at successes and failures. Especially in community setting, the development of a Collaborative Diabetes Management [CDM], Low Sugar Volunteers [LSVs], core-community working group, vigorously participated in all community activities to manage diabetes disease and its relevance. CIPP model was used to guide an evaluation of all activities that happened during a CDM development. Context, input, process, product, and appraisal sustainability were presented via LSVs community driven. CDM via community participation strategies prejudiced community health impacts, community health policy, and community sustainability. Moreover, various findings from CDM development influence actions and community direction either immediately or in the future.